Genetic variations of the L2 gene in human papillomavirus (HPV) type 16 from cervical cancer patients in Sumatra region, Indonesia - Maya Savira; Analdi Farniga; Zidny Ilmiah; Rachmadina Rachmadina; Ika Agus Rini; Rahmat Azhari Kemal; Azza E Mahargyarani; Muhammad Z Admiral; Amru Sofian; Renardy Reza Razali; Donel Suhaimi; Andani Eka Putra (Narra J, 2025)
gene may reflect regional viral evolution and has potential implications for future vaccine development.
Keywords: Cervical Cancer and HPV Research; Animal Virus Infections Studies; Hepatitis B Virus Studies